FinTech Literacy and Entrepreneurial Intention among MSMEs: Trust as Mediator and Perceived Risk Moderator Effects Model - Suryo Budi Santoso; Fatmah Bagis; Herni Justiana Astuti; Meydy Fauziridwan (Ilomata International Journal of Management, 2026)
The increasing integration of financial technology into MSME business activities has not always been accompanied by a corresponding growth in technology-based entrepreneurial intention, suggesting that technical competence by itself is insufficient to stimulate strategic forms of entrepreneurial behavior. This study integrates FinTech literacy, trust, and perceived risk within a single behavioral framework to explain entrepreneurial intention among MSMEs. Drawing on the Theory of Planned Behavior together with insights from technology adoption studies, trust is positioned as a mediating psychological mechanism, while perceived risk is examined as a contingency factor shaping the effectiveness of trust. Employing a quantitative explanatory design, information was gathered from 210 MSME owners along with managers in the Solo Raya and Yogyakarta Special Region and subsequently examined using the Partial Least Squares approach to Structural Equation Modeling (PLS-SEM). The results show that FinTech literacy does not directly influence entrepreneurial intention; however, it exerts a significant indirect influence via trust. Furthermore, perceived risk serves as a negative moderating factor in the relationship between trust and entrepreneurial intention, weakening its influence under high-risk perceptions. This research advances the digital entrepreneurship literature by showing that FinTech literacy operates primarily through affective and risk-related mechanisms rather than as a direct driver of intention, and by empirically establishing perceived risk as a boundary condition in the trust–entrepreneurial intention relationship in the MSME context of a developing economy. Practically, the findings highlight the need for FinTech literacy initiatives and regulatory frameworks that emphasize trust-building and risk reduction to foster sustainable entrepreneurial behavior among MSMEs.